(3JGQjN bSfWjfIs - (3CMeO Hf GdeHGQc Hf GdYWGQ GdbSfWjfj, GHf GdYWGQ,J (B1287 (3g` s
(3ChdgG (B:s
(3hHYO abO SCdfi GdeMHjf Cf bjO dg CNHQg bSfWjfg aCLHJg HbUhQi aGcJai efi HGdfRQ Gdbdjd s
(3BNQgG (B:s
(3aYfO Pdc fRd Edi GdeMdI Ydi YGOI GhdGI hONd bSfWjfg hJe dg GdCeQ hgPG fGJjSQ LeYg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B245 - (3U(B330s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B202s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B82 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B((3O (B709) s
Keywords: (3GdJGQjNs